ROLE OF PARACETAMOL AGAINST THE EROSIVE ACTION OF RECTIFIED SPRIT ON STOMACH IN ALBINO RATS - Draz, Umar; Janjua, M. Zahoor (Journal of Ayub Medical College Abbottabad, 1989)
ABSTRACT The protective role of paracetamol against rectified spirit (nonspecific injuring agent) on the gastric mucosa of albino rat was observed under dissecting as well as laboratory micro-scope. A dose of250 mg/kg body weight provided complete protection under dissecting micro-scope. However, gum acacia with rectified spirit treatment provided significant decrease in the erosion score. Under laboratory microscope a significant increase in the thickness of the mucosa was observed in combined treatment of paracetamol with rectified spirit as compared to rectified spirit alone or gum acacia with rectified spirit. A slight exfoliation and flattening of the surface epithelium may probably be due to increase in the secretory activity of chief cells. A significant increase in the secretory activity of the mucous neck cells in the group treated with rectified spirit plus paracetamol may be attributed to the increased bio-synthesis of prostaglandin from the mucous neck cell, which provides partial protective role against ulcerogenic agent.